O mecanismo de desenvolvimento limpo como mitigador do aquecimento global e a participação do Brasil - COTA, Raimundo Garcia (2011)
This study of economic-environmental relevance emerges from the problem of the Global Environment in order to analyze the Mechanism of Clean Development (MCD) as an efficient tool, which can contribute to the mitigation of the Greenhouse Effect Gases (GEG) through the fulfilling of emission reduction goals pre-established by Kyoto Protocol. One examines the participation of Brazil as a hosting country of MCD projects. One concludes that, although the implementation of the MCD reduces the global cost of reduction of greenhouse gases emissions by developed countries and supports initiatives which promote sustainable development, the lacking of major specificity in the rules of the mechanism can open precedents to the right of polluting. One understands that the mechanism cannot be restricted only to the fulfillment of goals, but it is fundamental that it works as discouragement of pollution in its origin, according to the proposal of sustainability, north of the weather environmental policy.